Malaysian Child Social Workers’ Perceptions of Emotions in Decision-making Processes - Habibie Ibrahim; Sally Johnson; Philip Giligan; Jones Adu-Gyamfi (Asian Social Work Journal, 2018)
The present research aimed to investigate the perceptions of the Malaysian Child Social Workers on emotions in their professional practice i.e. decision-making processes. Traditionally, decision-making is viewed as a rational process where reason indicates the best way to achieve a goal. However, many philosophers, neuroscientists and psychologists emphasise that the role of emotions in decision making is not exempted. The overall research strategy was ethnographic. The researchers used a mixture of methods including individual interviews, participant observation, and a questionnaire. The research was conducted in three locations in Malaysia: Kuala Lumpur, Petaling and Kota Kinabalu. Participants consisted of child protectors and rehabilitation officers from the Malaysia Welfare Department and medical social workers in hospitals. This paper presents an analysis of individual interviews in the three locations. A total of twenty-five interviews were conducted (twelve male, thirteen female; age range 29-51). Data were analysed using thematic analysis. The research findings revealed that the Malaysian child social workers tended to avoid emotions in their professional practice (i.e. decision- making processes), which might be due to the procedural practice. Based on the participants’ perceptions with regard to the use of emotions in decision-making proceses, the Malaysian child social workers’ understanding, knowledge and terms pertaining to emotions and their contributions in decision making were seemingly confined to the negative effects of emotions. Emotions, however, were not only characterised as disruptive but also viewed as having their ‘rationality’.